PENGARUH PEMBERIAN CAHAYA TERHADAP WAKTU PERKECAMBAHAN TANAMAN BAYAM (Amaranthus Spinosus) - Indasari, Nur; Hernawati, Hernawati; Hamzah, Ria Rezki (JFT : Jurnal Fisika dan Terapannya, 2018)
Research has been done on plant germination with the addition of LED light with variations in color, lamp distance, and type of lamp with the aim to determine the growth of green spinach and red spinach when treated at night. This research was carried out by planting green spinach and red spinach in 10 polybags in each light. Every 10 polybags of spinach are illuminated by lights with red, blue, yellow, and polybag colors without the addition of light. Furthermore, at the distance of the lamp 60 cm, 50 cm, 40 cm, 30 cm, 20 cm, 10 cm and without the addition of light. And for this type of LED lights, incandescent, neon and without the addition of light. Illumination of light is carried out at night for 3 hours. Spinach germination is observed every day to find out the time of germination, and is controlled at all times for plant maintenance by watering the plants so that soil moisture remains controlled. The data obtained from this study were analyzed by graphical analysis of the relationship of light to the time of germination of green spinach and red spinach plants. The results of this study indicate that the light influences the red LED light, distance of 10 cm and 20 lights and the type of fluorescent lamp on the germination of spinach plants. While the influence of other lights gives the same effect on spinach plants, because the growth is rather slow compared to plants that are illuminated in red lights, the distance of the lights is 10 cm and 20 cm, and the type of fluorescent lights.